Amikacin Dosing for MDR Tuberculosis: A Systematic Review to Establish or Revise the Current Recommended Dose for Tuberculosis Treatment. (28th November 2018) - Sturkenboom, Marieke G G; Simbar, Noviana; Akkerman, Onno W; Ghimire, Samiksha; Bolhuis, Mathieu S; Alffenaar, Jan-Willem C
Abstract: Background: Amikacin has been used for over 40 years in multidrug resistant tuberculosis (MDR-TB), but there is still debate on the right dose. The aim of this review was to search relevant pharmacokinetic (PK) and pharmacodynamic (PD) literature for the optimal dose and dosing frequency of amikacin in MDR-TB regimens trying to optimize efficacy while minimizing toxicity. Methods: A systematic review on the value of amikacin as second-line drug in the treatment of MDR-TB was performed. Results: Five articles were identified with data on PK, hollow-fiber system model for TB and or early bactericidal activity of amikacin. Despite the long period in which amikacin has been available for the treatment of MDR-TB, very little PK data is available. This highlights the need for more research. Conclusions: Maximum concentration (Cmax) of amikacin related to MIC proved to be the most important PK/PD index for efficacy. The target Cmax/MIC ratio should be 10 at site of infection. Cumulative area under the concentration-time curve (AUC) corresponding with cumulative days of treatment was associated with an increased risk of toxicity.